Sosialisasi Bahaya Konsumsi Minuman Manis di Sekolah Dasar Negeri No.101946 Bengabing Kecamatan Pegajahan - Rahmadi Ali; Ikhsan Baihaqi; Siti Masyitha; Afifah inaya; Aprillia Sanggita; Najwa Faradilla Azzahra; Rahmi Puspa Lily; Anim sanggita; Siti Halizah Harahap (Comit: Communication, Information and Technology Journal, 2025)
Excessive consumption of sugary drinks can have detrimental effects on health, such as diabetes, obesity, tooth decay, and others. Therefore, it is important to conduct socialization and education regarding the dangers of excessive consumption of sugary drinks, by limiting the consumption of sugary drinks and sugar intake. This research uses a qualitative descriptive method, which is a research process that produces descriptive data in the form of written or spoken words from people and observable behaviors, conducted at State Elementary School No. 101946 Bengabing, Pegajahan District. The socialization was carried out in several stages, covering the following aspects: Initial study, Planning, Site observation, Problem identification, Problem-solving, Developing materials, Implementation/presentation, Final activity report, Presentation of the final activity report, Evaluation of results. The research subjects in this socialization numbered 20 people. The results obtained from the socialization are: Increased ability of grade 4 students in choosing healthy drinks to consume. Increased awareness among grade 4 students about sugary drinks, the sugar content in them, and the types of sugary drinks consumed by grade 4 students in excess.